The use of films as therapeutic strategy in clinical practice (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
The use of film in psychotherapy, although not new, is still not widespread in scientific circles. To enlarge this issue, this article aimed to demonstrate the use of film as a complementary therapeutic strategy to traditional behaviors in clinical practice, using a case report in which the client had difficulty to keep in lasting relationships. Thirty-five sessions were conducted, and observed that the use of films involved similar topics to complaints provided the understanding of establishers and sponsors variables the behavioral pattern’s customer. It was noted greater engagement thereof, expansion of the behavioral repertory and modification of maintaining contingencies of problem behaviors. Although this case allows broad discussion about effectiveness of this resource, points up the importance of promoting more scientific evidences to support it in fact.
Keywords: cinematherapy therapeutic resources; interpersonal relationships